A Manganese Catalyst for Highly Reactive Yet Chemoselective Intramolecular C(sp(3))—H Amination - Paradine, Shauna M. (Nat Chem, 2015)
C—H bond oxidation reactions underscore the existing paradigm wherein high reactivity and high selectivity are inversely correlated. The development of catalysts capable of oxidizing strong aliphatic C(sp(3))—H bonds while displaying chemoselectivity (i.e. tolerance of more oxidizable functionality) remains an unsolved problem. Herein, we describe a catalyst, manganese tert-butylphthalocyanine [Mn((t)BuPc)], that is an outlier to the reactivity-selectivity paradigm. It is unique in its capacity to functionalize all types of C(sp(3))—H bonds intramolecularly, while displaying excellent chemoselectivity in the presence of π-functionality. Mechanistic studies indicate that [Mn((t)BuPc)] transfers bound nitrenes to C(sp(3))—H bonds via a pathway that lies between concerted C—H insertion, observed with reactive noble metals (e.g. rhodium), and stepwise radical C—H abstraction/rebound, observed with chemoselective base metals (e.g. iron). Rather than achieving a blending of effects, [Mn((t)BuPc)] aminates even 1° aliphatic and propargylic C—H bonds, reactivity and selectivity unusual for previously known catalysts.